HUBUNGAN PROFESIONALISME PENDIDIK TK DENGAN KINERJA PENDIDIK DI TK RAYON IV KOTA DUMAI - Ranirizal Ranirizal (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
The performance of good educators will be demonstrated quantitatively and qualitatively through the process of having responsibility in their profession. This performance will be relevant to their professionalism as teachers or educators. Educator performance development is a very decisive factor in the success of the education and learning process. In fact, at TK Rayon IV, Dumai City, there were still low competency standards possessed by educators. The intended competency standard is from the standard academic qualifications and four competencies that must be possessed by a kindergarten educator, namely pedagogic, professional, social and personality competencies. This is evidenced by educators not yet mastering learning material with the maximum known when the learning process educators are not able to explain well the subject matter, and educators have not shown maximum performance in carrying out their duties and functions. The purpose of this study is to see whether there is an influence between teacher professionalism on teacher performance at TK Rayon IV, Dumai City. The results of the study prove that the value of Sig (2-tailed) professionalism on the performance of educators is .768 with a significant level of results of 0.000, then the calculation shows that 0.000 is smaller than 0.05. This means Ha is accepted and Ho is rejected. Statistically, it proves that there is a significant relationship between the professionalism of kindergarten educators and the performance of educators in TK Rayon IV, Dumai City